Scanning microwave impedance microscopy and its applications: A review - Diego Tami; Douglas A. A. Ohlberg; Cássio Gonçalves do Rego; Gilberto Medeiros-Ribeiro; Jhonattan C. Ramirez (APL Materials)
Scanning microwave impedance microscopy (sMIM) has become a powerful tool for nanoscale characterization, utilizing microwave frequencies to probe the material properties of diverse systems with remarkable spatial resolution. This review offers an in-depth analysis of the foundational principles, technological advancements, and broad applications of sMIM. By harnessing near-field microwave interactions between a sharp metallic probe and the sample, sMIM enables simultaneous acquisition of both real (resistive) and imaginary (capacitive) components of the reflected signal, providing detailed insights into the local permittivity and conductivity of materials at the nanoscale. We address critical challenges, including impedance matching, probe–sample interactions, and the influence of environmental factors such as surface water layers and meniscus formation on resolution and contrast. Recent advancements in finite element modeling and the application of lumped-element circuit models have further enhanced the precision of signal interpretation, enabling more accurate analysis of complex systems. This review highlights sMIM’s wide-ranging applications, from material science and semiconductor diagnostics to biological systems, showcasing its ability to perform non-destructive, high-resolution imaging down to the single-digit nanometer scale. These capabilities position sMIM as an indispensable tool for advancing future innovations in nanotechnology and related fields.